Food waste in EU countries - Vida , Viktória; Kovács , Tünde Zita; Nagy , Adrián Szilárd; Madai , Hajnalka; Bittner, Beáta (Applied Studies in Agribusiness and Commerce, 2022)
The biggest challenges of our time include meeting the demand growth resulting from the explosion in population growth and achieving sustainable management. In terms of food, the most significant problem is, on the one hand, that a large part of the population is hungry and, on the other hand, excessive food waste, which results not only in wasted food but also in wasted resources used for its production, transport, packaging and storage. Do to this the unconsumed food has a profoundly negative impact on the environment and the economy. There is a pressing need to prevent and reduce food waste to transition to a resource-efficient Europe. In this study, we would like to show how food waste changes in different countries, focusing on Europe. Our results show a significant discrepancy between Member States' data and where waste is generated. We find no significant correlation between GDP per capita and total food waste, but we find a moderately strong correlation between GDP per capita and restaurant waste at the point of generation.JEL code: M21